Visiting Jackie And Marty Hijmans, Edwards, Colorado - Watkins, Howard::::::::: (1982)
Marty Hijmans holding Carey Hijmans and Howard Watkins looking at long beam; Adam Watkins touching five foot level on installed four by twelve deck beam